POSSIBLE PHARMACOLOGICAL BASIS FOR ANTITHROMBOTIC EFFECT OF GLYCYRRHIZA GLABRA IN SPRAGUE DAWLEY RATS (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
It has been previously identified that 3-aryl comarin derivative, GU-7 isolated from Liquorice posses Antiplatelet activity. It inhibits platelet aggregation by increasing intraplatelet cyclic AMP concentration. Here we report the in-vivo effects of extract of Glycyrrhiza glabra and also the combined effect with Vitamin K and Heparin. Extract of Glycyrrhiza glabraincreased the bleeding time when given in the doses of 180 mg/kg and 360 mg/kg. Blood loss was evaluated 60 minute later as a function of absorbance at 540 nm due to hemoglobin content in water solution. Altogether data indicates that Glycyrrhiza glabra is an effective anti thrombotic agent in vivo, which may account for its known pharmacological properties.